Clinical characteristics, management, and outcomes of cadmium poisoning: a systematic review of case reports and case series - Shao, Zekai; Wang, Minyan; Mandizadza, Oscar Onayi; Ji, Conghua (Frontiers in Public Health, 2025)
ObjectiveThis paper synthesizes case reports and series to outline the clinical features, diagnosis, treatment, and prognosis of cadmium poisoning. It offers structured evidence to improve understanding, early diagnosis, and clinical management, aiding healthcare professionals in prevention and intervention.MethodsThe study protocol has been registered in the PROSOPERO system (CRD420251128280). We independently searched PubMed, Scopus, and Cochrane databases using keywords including “cadmium poisoning,” “case report,” and “case series.” Only English-language case reports and series with confirmed or highly suspected cadmium poisoning were included, up to May 2025. Animal studies, reviews, and articles lacking individual patient data were excluded. Additional references were identified from the bibliographies of retrieved articles. Study quality was assessed using the JBI tool for case reports/series.ResultsAmong the 12 included studies, there were a total of 17 patients. We found that cadmium poisoning primarily affects adult males and is often associated with occupational exposure. Common risk factors include smoking and alcohol consumption. The study also found that low iron stores exacerbate cadmium poisoning. Diagnosis relies on a combination of clinical diagnostic tests, blood and urine tests, chest X-rays, kidney ultrasounds, bone density measurements, and skeletal imaging. The treatment plan includes the use of chelating agents to reduce cadmium levels in the body and antibiotics to maintain the patient’s condition. For patients with concurrent lung and kidney involvement, mechanical ventilation and continuous renal replacement therapy (CRRT) may be required. Additionally, for patients with osteochondropathy, supplementation with calcium and vitamin D is recommended. While most patients have a favorable prognosis, fatal cases due to respiratory failure or renal failure have been reported.ConclusionThis review emphasizes that cadmium poisoning is rare and complex, with non- specific symptoms and a tendency to cause organ damage. Therefore, it is necessary to enhance clinical vigilance. Occupational exposure highlights the need for public health surveillance. Diagnosis relies on blood or urine cadmium testing, which is crucial for guiding treatment. Although the condition is relatively uncommon and most patients have a favorable prognosis, the risk of severe complications and mortality underscores the importance of timely and individualized treatment. Further research is needed to optimize management and improve long-term outcomes.Systematic review registration(registration number: CRD420251128280).